2009
DOI: 10.1002/iroh.200811159
|View full text |Cite
|
Sign up to set email alerts
|

Leaf‐Litter Mixtures Affect Breakdown and Macroinvertebrate Colonization Rates in a Stream Ecosystem

Abstract: Previous work in terrestrial and aquatic ecosystems has suggested that the relationship between breakdown rates of leaf litter and plant species richness may change unpredictability due to nonadditive effects mediated by the presence of key-species. By using single-and mixed-species leaf bags (7 possible combinations of three litter species differing in toughness; common alder [Alnus glutinosa], sweet chestnut [Castanea sativa], and Spanish oak [Quercus ilex ilex]), I tested whether leaf species diversity, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
4
12
1
Order By: Relevance
“…The leaf breakdown rates for the two species were similar to those found for other species in tropical regions (Gonç alves et al, 2006;Chara et al, 2007;Moretti et al, 2007) but lower compared to studies in temperate zones (Braatne et al, 2007;Baudoin et al, 2008;Abelho, 2009). The highest breakdown rates found in streams of temperate ecosystems may be related to lower concentrations of recalcitrant compounds in the detritus (Ardón et al, 2009).…”
Section: Breakdown Rates and Characteristics Of Leaf Detritussupporting
confidence: 63%
“…The leaf breakdown rates for the two species were similar to those found for other species in tropical regions (Gonç alves et al, 2006;Chara et al, 2007;Moretti et al, 2007) but lower compared to studies in temperate zones (Braatne et al, 2007;Baudoin et al, 2008;Abelho, 2009). The highest breakdown rates found in streams of temperate ecosystems may be related to lower concentrations of recalcitrant compounds in the detritus (Ardón et al, 2009).…”
Section: Breakdown Rates and Characteristics Of Leaf Detritussupporting
confidence: 63%
“…The breakdown rates of alder (k = −0.0430 day −1 ) and poplar (k = −0.0220 day −1 ) decomposing in the stream were fast according to the classification of Petersen and Cummins (1974). Decomposition rate of alder was similar to rates previously obtained in the same stream (Abelho, 2009;Gonçalves and Canhoto, 2009) and faster than most values reported in literature for the same or similar leaf species (e.g. Abelho, 2001;Canhoto and Graça, 1996).…”
Section: Aldersupporting
confidence: 81%
“…In this study, we used mixed litter bags [39] suggested that these differ in the decomposition rate in relation to litter bags of unique species, but still found that there is a similarity in colonization patterns of macroinvertebrates. However, Cortes et al (1997) [40] concluded that, in streams, the food availability is high and there is no particular reason for the macroinvertebrates aggregate in litter bags.…”
Section: Discussionmentioning
confidence: 99%